Kontribusi Panjang Tungkai dan Daya Ledak Otot Tungkai Terhadap Lompat Jauh Gaya Jongkok pada Siswa MAN Kotabaru - M. Imran Hasanuddin (STKIP Paris Barantai, 2020)
This research is a type of descriptive research. This study aims to determine: (1) whether there is a contribution of leg length to the squat-style long jump made by the PutraMAN Kotabaru Students (2) whether there is a contribution there is a contribution of the leg muscle explosive power to the squat-style long jump by the PutraMAN Kotabaru Students. (3) is there any contribution of the contribution of leg length and leg muscle power to the squat style long jump made by PutraMAN Kotabaru Students The population is all of the male students of MAN Kotabaru. The samples used are the male students of MAN Kotabaru, as many as 50 people. The technique of determining the sample is by random selection by lottery (Simple Random Sampling). The data analysis technique used is descriptive analysis and inference analysis through the SPSS 22 program at a significance level of Î± 0.05. The results showed that; (1) there was a contribution of leg length to squat style long jump made by PutraMAN Kotabaru Students by 18.1%. ., (3) there was a contribution of leg length and leg muscle explosive power to squat-style long jump made by male students of MAN Kotabaru by 46.4% with a value of F: 20.370 and sig (p) = 0.000. Keywords: Leg length, leg muscle explosive power and long jump squat style